TRANSFER OF LAND RIGHTS THROUGH HIBAH BASED ON LAWS AND REGULATIONS - I Gusti Agus Yuda Trisna Pramana; Ida Bagus Wirya Dharma; I Wayan Antara; I Dewa Gede Budiarta (NOTARIIL Jurnal Kenotariatan, 2025)
The topic of transitioning land rights through grants has high urgency, considering that land is a legal object of economic value and is increasingly needed in the era of globalization. However, there is a gap between theory and practice related to the implementation of the registration of granted land rights. Although laws and regulations, such as Government Regulation Number 24 of 1997, regulate the obligation to register land that has been transferred, practice on the ground shows that there are legal loopholes that allow the transfer of land rights without proper registration, thus potentially harming the parties involved. The purpose of this study is to analyze the mechanism of transfer of land rights through grants and the obstacles that arise due to unclear rules related to land rights registration. The method used in this study is a normative juridical research that analyzes laws and regulations and practical applications in the process of registering land grants by the Land Deed Making Officer (PPAT). The main findings of this study show that the lack of provisions governing in detail the mechanism of grant registration leads to legal loopholes that can be exploited for the transfer of land to other parties, including through the imposition of dependent rights. The results of this study suggest the need for further structuring regarding the regulations governing land grant registration to ensure legal certainty and avoid potential legal problems in the future.